Analysing the shoot and roots response of wheat in a soil environment under variable water and nitrogen supply - Cousins, Olivia H. (2020)
Increasing water variability and the cost and sustainability of nitrogen (N) fertiliser use are of growing concern globally. Soil water supply directly and indirectly regulates soil N availability. As a result, plants have to adapt their shoots and roots in order to optimise water and N uptake. This thesis seeks to investigate the interactive effects of water and N supply on important soil properties and the growth and physiology of two Australian wheat varieties, Gladius and Kukri, both possessing phenotypic traits and water/N use efficiencies. This research seeks to explore and discuss how soil moisture affects soil N dynamics, and subsequently how different root traits affect N and water acquisition in a complex soil environment.